O ensino de ciências na educação infantil, o currículo e as percepções dos professores da rede pública municipal de ensino de Cascavel PR - Silva, Eliane Theinel Araujo (2023)
The Teaching of Science in Early Childhood Education is configured as an open field for research and innovations in the classroom’s educational actions, which often ends up being set aside as an educational function in this stage of schooling. Currently, given the increasing importance of a didactic, this teaching presents itself as challenging to the teachers, considering the need to equip the child to gradually approximate their empirical knowledge to aspects of scientific knowledge. Science has been through many transformations temporally, and the way of teaching it raises innovations in educational work, developing an education proposal that promotes learning by a new dynamic related to relevant aspects of the child’s structure of knowledge. Therefore, this study’s core issue is investigating how the teaching and learning process has been happening for preschool children considering the curriculum and the teaching of science in the perceptions of teachers from the Municipal Public Education System of Cascavel-PR. To accomplish this goal, we proposed a dialogue between the teaching of science guidelines and early childhood education, establishing a research of qualitative and exploratory approach. The collection of data is centered around the semistructured interviews made with this stage’s teachers, analyzed in light of the Textual Discourse Analysis (TDA). As for document analysis, we utilized the Curriculum for the Municipal Public System of Cascavel - early childhood education, curricular component of science and official documents of specific legislation, seeking to comprehend aspects of curricular organization and the teaching and learning processes in early childhood education. The results of this research revealed the importance of a curriculum for early childhood education, reinforced the necessity of continuous formation and study groups, striving for researcher teachers so that the teaching of science in early childhood education begins to configure itself as a teaching centered in scientific knowledge, and be significant to the children. We emphasize that it is still a field to be explored and highlight the importance of the continuity of research with this subject, addressing discussions on the curriculum and the teaching of science in early childhood education, towards the developmental teaching.